Remote Working During Pandemic of COVID-19 In Poland: Selected Aspects - Anna BARWINSKA-MALAJOWICZ; Iwona BAK; Radoslaw PYREK (Communications of International Proceedings, 2021)
This article represents the actual need to compare and systematizing definitions of selected flexible forms of employment such as teleworking and remote working. It presents their legal interpretation and also using its rates in practice. The main purpose of this study is to introduce certain aspects of remote working in pandemic times of COVID-19 in Poland. Statistical data were analysed that were collected by Central Statistical Office in Warsaw and Eurostat in years 2020 – 2021 (quarterly data). The article contribute actual academic discussion about the influence of pandemic to flexible forms of employment and also doing remote working in Poland. Presented research results give wide opportunities in further analysis and interpretation. They can become a contribution to exacerbate research in taken issue. The results of those analysis can help not only employers but also people working in understanding the impact of pandemic of employment market flexibility. From one side those information can be useful for employers on deciding about more flexible forms of employment and from the other side development of workers awareness as to flexible forms of work. Therefore, this study complement research gap in this area.
Keywords: Poland; labour market; flexible forms of employment; teleworking; remote working